Conflictual potential of Soviet Borders - Svetlana Yurievna Glushkova, Liliya E Ilikova, (Opción, 2019)
The authors examine the conflictual potential of soviet borders, as well as their influence on the social processes on former USSR republics via the comparative approach, historical and ethnological methods. In result, in every national Republic during the ethnic revival proceeded the process of writing alternative history, which would reveal the Soviet period in the history and reappraise the pre-Soviet period. In conclusion, all former Soviet republics – now independent States - are in the period of post-Soviet history and under influence of the USSR history. Under certain conditions of ethnic mobilization, such conflicts can be running at any time.